ANALISA PENGARUH PANJANG PIPA INLET DAN PANJANG PEGAS KATUB BUANG TERHADAP PERFORMANCE POMPA HIDRAM - Santoso, Edi; Utomo, Gatut Priyo; Martini, Ninik (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
Hidram pump is one of the water pumps are energy efficient andenvironmentally friendly. Pump hidram an effective technology in the field ofenergy pumping by using the momentum of the water (water hammer) to raisethe water, so the pump hidram one water pump that does not use fuel andelectricity. Effectiveness hidram pump performance is affected by severalparameters such as the diameter of the pipe, reservoir height, exhaust valve, theair tube on hidram pump, inlet pipe length. This study aimed to observe andanalyze the effect on the length of the inlet pipe to the pump hidram highdischarge pumps and pumping. This research method through the design of thepump installation hidram and observation influence the inlet pipe length (6 m, 8m, 10 m), and the observation of the effect of the length of the exhaust valvespring (7 cm, 8 cm, 10 cm) to the pressure value (H) and the value of discharge(Q) to the pump performance hidram. The test is performed in ProductionProcess Laboratory August 17, 1945 University of Surabaya. The longer thepipe, the flow in the pump inlet hidram (Q) generated will be even greater. So inthe above study also directly proportional to the value of head (H) anddischarge rate (Q) on the pump performance hidram. So the value of theexisting pressure in the pump hidram with maximum value is generated headwith value - average (H) 1.41 bar and the discharge of water produced with -average (Q) 21 liters / min. This is because the moment of greatest impact onthe water valve.Keywords: Pump Hidram